The Baskalamantra-Upanisad and the Bhagavadgita - Ježić, Mislav (Array, 2002)
When comparing the setting, the dialogue, and the theses of Baskalamantra-Upanisad and the Bhagavadgita, the parallels can demonstrate that many concepts of the later Visnuite theology were adopted from the late Vedic Indraic theology. In the older stages of the epics the supreme divinity is Indra, but the texts are heroic poetry and lack any theology. Later on, when the epics develop religious features, the supreme divinity is already Visnu and not Indra. Therefore the Baskalamantra-Upanisad may be a document of the late Vedic Indraic theology underlying the older stages of the epics, but lacking in them any explicit elaboration.